1977
DOI: 10.3177/jnsv.23.447
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and folate binding protein in pregnancy.

Abstract: SummaryFolic acid and folate binding protein (FABP) concentrations were determined in 208 pregnant women as well as in 50 non-pregnant women. Serum folate levels in pregnant women were significantly lower than those of the non-pregnant group. Anaemic pregnant women also had lower serum folate concentrations than those of the non-anaemic pregnant women. Ninetyeight of 208 (47.1%) pregnant women had serum folate levels of less than 4ng/ml. No significant dierence in red cell folate concentration between the preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Achanta et al (2007) found no significant effect on FBP concentration after pasteurization using ELISA. In contrast, Areekul et al (1978) and Kohashi et al (1985) reported more than 90% reduction in folate binding capacity in pasteurized milk. A possible explanation of these conflicting results might be that the conditions for pasteurization closely resemble the denaturation temperature for FBP in milk.…”
Section: Introductionmentioning
confidence: 62%
“…Achanta et al (2007) found no significant effect on FBP concentration after pasteurization using ELISA. In contrast, Areekul et al (1978) and Kohashi et al (1985) reported more than 90% reduction in folate binding capacity in pasteurized milk. A possible explanation of these conflicting results might be that the conditions for pasteurization closely resemble the denaturation temperature for FBP in milk.…”
Section: Introductionmentioning
confidence: 62%